Question
Wed October 24, 2012 By:

Solve bu quadratic formula

Expert Reply
Wed October 24, 2012
Answer : Given : equation p2x2 +(p2-q2)x - q2 =0 
To find the solution of x using quadratic formulae
 
a = p2  , b=p2-q2 ,c= - q2 
 
therefore x = [-b + (b2-4ac)1/2 ]/2a ,[-b  - (b2-4ac)1/2 ]/2a
 =[(p2-q2) + ((p2-q2)2 - 4(p2)(-q2))1/2] / 2p2 and
 [(p2-q2) - ((p2-q2)2 - 4(p2)(-q2))1/2] / 2p2
 
as we know that (A+B)2 =(A-B)2 +4AB
=> (p2+q2)2 = (p2-q2)2 +4p2q2
 
=> x = ([(p2-q2) + ((p2+q2)2)1/2] / 2pand ([(p2-q2) - (p2+q2)2)1/2] / 2p2
 
=> x =  [(p2-q2) + (p2+q2)] / 2p2 and [(p2-q2) -(p2+q2)] / 2p2
=> x = q2/p2 and -1 Answer
Related Questions
Tue February 14, 2017

Fri January 27, 2017

1/a+b+x=1/a +1/b +1/x

Ask the Expert